2020
DOI: 10.3389/fmedt.2020.615494
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Mechanisms of Synergistic Action of Two Magainin Antimicrobial Peptides

Abstract: The study of peptide-lipid and peptide-peptide interactions as well as their topology and dynamics using biophysical and structural approaches have changed our view how antimicrobial peptides work and function. It has become obvious that both the peptides and the lipids arrange in soft supramolecular arrangements which are highly dynamic and able to change and mutually adapt their conformation, membrane penetration, and detailed morphology. This can occur on a local and a global level. This review focuses on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 191 publications
(384 reference statements)
0
29
0
Order By: Relevance
“…The structure of α-helical peptides is lost in solution, but acquires an amphipathic helical structure in contact with a biological membrane. Frog magainins belong to this class [ 21 ]. On the other hand, β-Sheet peptides contain two to ten cysteine residues that form one to five interchain disulfide bonds.…”
Section: Classification Of Antimicrobial Peptidesmentioning
confidence: 99%
“…The structure of α-helical peptides is lost in solution, but acquires an amphipathic helical structure in contact with a biological membrane. Frog magainins belong to this class [ 21 ]. On the other hand, β-Sheet peptides contain two to ten cysteine residues that form one to five interchain disulfide bonds.…”
Section: Classification Of Antimicrobial Peptidesmentioning
confidence: 99%
“…At the same time, it should be noted that biological membranes mainly consist of unsaturated lipids. It has been shown that in membranes that carry unsaturations, both peptides are aligned along the bilayer surface [173]. Consequently, a mechanism for synergistic antibacterial activities should necessarily consider the last fact.…”
Section: Cooperation Among Amps: Synergismmentioning
confidence: 99%
“…The pronounced antimicrobial activities of cationic amphipathic peptides including LAH4 sequences have been associated with the perforation of microbial membranes [10,18,51,52,55]. Indeed, under conditions where the peptides align along the membrane surface [11,13,20], high concentrations of LAH4 peptides result in the lysis of lipid bilayers [17,22].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Cecropins and magainins were among the first peptides from higher organisms for which a wide range of antimicrobial activities was described [8]. Early on after their discovery, biophysical approaches showed that these peptides are aligned along the surface of lipid bilayers rather than forming channels made of transmembrane helical bundles, as had initially been considered [9,10]. To further investigate the interaction contributions that govern peptide-membrane interactions, histidine-rich peptides were designed by assembling an alanine-leucine hydrophobic core, interspersed with four histidines (LAH4) that all align at one face in a helical conformation, and two lysines at each terminus [11].…”
Section: Introductionmentioning
confidence: 99%